(untitled) (Journal of Economic Additions, 2025)
This article examines the topic of government support in Algeria, its objectives, various forms and mechanisms, its economic burdens, and its repercussions on the performance of business organization. The results indicate that some objectives have been achieved, but they also highlight several shortcomings that hinder the efficient performance of this organization, emphasizing the need for review and reform. Keywords: Government support; Business organization; Performance of business organization Jel Classification Codes : M100, H250.